Systematic Pharmacology and GEO Database Mining Revealed the Therapeutic Mechanism of Xuefu Zhuyu Decoration for Atherosclerosis Cardiovascular Disease - Liang, Bin; Xiang, Yang; Zhang, Xiaokang; Wang, Chen; Jin, Bingyu; Zhao, Yue; Zheng, Fang (Frontiers in Cardiovascular Medicine, 2020)
Background: Xuefu Zhuyu decoration (XFZYD), as a traditional Chinese compound recipe, has been used to treat atherosclerosis cardiovascular disease (ASCVD) for thousands of years in China, but its effective compounds and underlying treatment molecular mechanism remains promiscuous, which severely limits its clinical application. Methods: The effective components and its targets of XFZYD were predicted and screened based on the TCMSP database. The candidate therapeutic targets of ASCVD were screened by Pharmacogenomics Knowledgebase (PharmGKB) and Comparative Toxicogenomics Database (CTD). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses for target proteins were performed using DAVID database. Subsequently, protein-protein interaction (PPI) analyses were conducted using the STRING database. Differentially expressed genes in GSE71226 were identified using GEO2R. Finally, molecular docking was performed by Schrodinger software. Results: A total of 108 effective compounds and 137 candidate therapeutic targets were screened. Analyzing the relationships among effective compounds, candidate therapeutic targets, and signaling pathways, the therapy mechanism of XFZYD for ASCVD were mainly reflected in the protection of vascular endothelium, anti-inflammatory, antioxidant stress, etc. Moreover, the expression profile in GSE71226 supported our findings, while molecular simulation docking results also demonstrated the reliability of the predicted results. Conclusions: This study demonstrates the therapeutic potential of XFZYD for the treatment of ASCVD based on systemic pharmacology, which could provide a guiding principle for its clinical application as well as valuable insights for further drug discovery.